2015
DOI: 10.1155/2015/530957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe3O4Nanoparticles on Skin Tumor Cells and Dermal Fibroblasts

Abstract: Iron oxide (Fe3O4) nanoparticles have been used in many biomedical approaches. The toxicity of Fe3O4 nanoparticles on mammalian cells was published recently. Though, little is known about the viability of human cells after treatment with Fe3O4 nanoparticles. Herein, we examined the toxicity, production of reactive oxygen species, and invasive capacity after treatment of human dermal fibroblasts (HDF) and cells of the squamous tumor cell line (SCL-1) with Fe3O4 nanoparticles. These nanoparticles had an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…This method is most notably used in the fight against cancer, where nanoparticles are an effective tool in localized chemotherapy. By delivering the therapeutic preparation locally, it is retained longer in the affected organ, which reduces the undesirable effect on the rest of the body [40][41][42]. Hu et al confirmed the effectiveness of arsenic trioxide nanoparticles in the fight against malignant liver cancer.…”
Section: Drug Carriersmentioning
confidence: 99%
“…This method is most notably used in the fight against cancer, where nanoparticles are an effective tool in localized chemotherapy. By delivering the therapeutic preparation locally, it is retained longer in the affected organ, which reduces the undesirable effect on the rest of the body [40][41][42]. Hu et al confirmed the effectiveness of arsenic trioxide nanoparticles in the fight against malignant liver cancer.…”
Section: Drug Carriersmentioning
confidence: 99%
“…81 Many reports have shown that metallic NPs can significantly enhance the formation of ROS in skin cells. 8,82,83 Increased NO/ NO 2 and decreased GPx in fibroblasts and HaCaT cells have been observed after exposure to metallic NPs, indicating that NPs caused inflammatory responses and metabolic changes. Additionally, NPs affected the gene expression of SOD and GPx.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…7 Fe 3 O 4 NP-based cancer therapy is increasingly used in the biomedical field, because such nanoscale NPs can easily enter tumor cells and lead to apoptosis or necrosis. 8 Metallic NPs, such as AuNPs and CuNPs, were introduced to the dermatology field for the prevention and treatment of infections and wound healing, because of their excellent antibacterial properties. 9 All these aspects have greatly increased skin exposure to metallic NPs.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of Fe2O3NPs on skin tumor cells increases ROS and eliminates cancer cells, but no significant toxicity on healthy cells has been reported for these NPs [128].…”
Section: Metal Oxide Npsmentioning
confidence: 99%